Bioremoval of Lead and Cadmium by the Alga westillopsis prolifica - Kadhim Al-Hussainy, Abdulhadi; Kamil Al-Mayaly, Ithar (Iraqi Journal of Science, 2023)
Westiellopsis prlifica was exposed to 1, 2, 3, 5, 7 and 10 ppm from both lead & Cadmium, in order to measure their capacity to remove these metals from the polluted aquatic environment and to study its ability to tolerant them. The algae were grown under optimum conditions.Westiellopsis prlifica had the ability to remove the lead with percentages about 31.57, 54.42, 62.35, 61.8, 57.02 and 68.34% for the concentrations 1, 2, 3, 5, 7 and 10 ppm, respectively, but it was found that these percentages were be better in the last day of the experiment for some of the concentrations 1, 2 and 3 ppm, While the tolerant of it to lead was up to the concentration 10 ppm.Westiellopsis prlifica appears ability to remove Cadmium with percentages 42.32, 52.07, 58.18, 57.6, 62.31 and 73.2% for the concentrations 1, 2, 3, 5, 7 and 10 ppm, respectively. But it is ability to tolerant was up to the concentration 10 ppm.